SWR1 chromatin remodeling complex prevents mitotic slippage during spindle position checkpoint arrest - Caydasi, Ayse Koca; Khmelinskii, Anton; Darieva, Zoulfia; Kurtulmus, Bahtiyar; Knop, Michael; Pereira, Gislene (Molecular biology of the cell, 2023)
Faithful chromosome segregation in budding yeast requires correct positioning of the mitotic spindle along the mother to daughter cell polarity axis. When the anaphase spindle is not correctly positioned, a surveillance mechanism, named as the spindle position checkpoint (SPOC), prevents the progression out of mitosis until correct spindle positioning is achieved. How SPOC works on a molecular level is not well understood. Here we performed a genome-wide genetic screen to search for components required for SPOC. We identified the SWR1 chromatin-remodeling complex (SWR1-C) among several novel factors that are essential for SPOC integrity. Cells lacking SWR1-C were able to activate SPOC upon spindle misorientation but underwent mitotic slippage upon prolonged SPOC arrest. This mitotic slippage required the Cdc14-early anaphase release pathway and other factors including the SAGA (Spt-Ada-Gcn5 acetyltransferase) histone acetyltransferase complex, proteasome components and the mitotic cyclin-dependent kinase inhibitor Sic1. Together, our data establish a novel link between SWR1-C chromatin remodeling and robust checkpoint arrest in late anaphase.